Impact of Direct Payment Reform of CAP 2014–2020 on the Economy of Agricultural Enterprises in Slovakia - Jana Prevužňáková; Peter Serenčéš; Marián Tóth (Polityki Europejskie, Finanse i Marketing)
New Common Agricultural Policy (CAP) in 2014-2020 introduces the changes in direct payments. Progressive reduction and capping of the payment will have impact mainly on big enterprises managing large land area. This is a reality in the Czech Republic and Slovakia. The paper is devoted to quantify and model the impact of forthcoming changes on the management of farms in Slovakia. As the results in chosen enterprises in Slovakia proved, these changes have a negative effect on the enterprises which are mainly the large ones with the low sales as well as the small salaries paid per hectare in comparison with the rest of the companies in Slovakia. In sense of effectiveness and rural development we do consider planned changes in direct payments as rational.